Ferric Sulfate and Proline Enhance Heavy-Metal Tolerance of Halophilic/Halotolerant Soil Microorganisms and Their Bioremediation Potential for Spilled-Oil Under Multiple Stresses - Al-Mailem, Dina M.; Eliyas, Mohamed; Radwan, Samir S. (Frontiers in Microbiology, 2018)
The aim of this study was to explore the heavy-metal resistance and hydrocarbonoclastic potential of microorganisms in a hypersaline soil. For this, hydrocarbonoclastic microorganisms were counted on a mineral medium with oil vapor as a sole carbon source in the presence of increasing concentrations of ZnSO4, HgCl2, CdSO4, PbNO3 CuSO4 and Na2HAsO4. The colony forming units (CFU) counted decreased in number from about 150 g-1 on the heavy-metal free medium to zero units on media with 40 to 100 mg l-1 of HgCl2, CdSO4, PbNO3 or Na2HAsO4. On media with CuSO4 or ZnSO4 on the other hand, numbers increased first reaching maxima on media with 50 mg l-1 CuSO4 and 90 mg l-1 ZnSO4. Higher concentrations reduced the numbers, which however, still remained considerable. Pure microbial isolates in cultures tolerated 200 to 1600 mg l-1 of HgCl2, CdSO4, PbNO3, CuSO4 and Na2HAsO4 in the absence of crude oil. In the presence of oil vapor, the isolates tolerated much lower concentrations of the heavy metals, only 10 to 80 mg l-1. The addition of 10 mg l-1, Fe2 (SO4)3, and 200 mg l-1 proline (by up to 2-3 fold) enhanced the tolerance of several isolates to heavy metals, and consequently their potential for oil-biodegradation in their presence. The results are useful in designing bioremediation technologies for oil spilled in hypersaline areas.